Clinical outcomes in HIV+/HCV+ coinfected kidney transplant recipients in the pre‐ and post‐direct‐acting antiviral therapy eras: 10‐Year single center experience. Issue 5 (4th April 2019) - Camargo, Jose F.; Anjan, Shweta; Chin‐Beckford, Nafeesa; Morris, Michele I.; Abbo, Lilian M.; Simkins, Jacques; Ciancio, Gaetano; Chen, Linda J.; Burke, George W.; Figueiro, Jose; Guerra, Giselle; Kupin, Warren L.; et al.
Abstract: Background: Previous studies have demonstrated inferior patient and graft survival following kidney transplant (KT) in HIV+/HCV+ coinfected patients compared to HIV+/HCV− recipients. However, these studies were conducted prior to the availability of direct‐acting antiviral (DAA) agents and data in the modern era are lacking. Methods: Single center retrospective study of HIV+/HCV+ coinfected KT recipients (2007‐2017). Outcomes were assessed for the pre‐DAA and post‐DAA (ie, after December 2013) eras including 1‐year patient survival, death‐censored graft survival, and acute rejection; and serious infections (defined as infections requiring admission to the intensive care unit during initial transplant hospitalization or re‐admission to the hospital after discharge) within the first 6 months post‐transplant. Results: A total of 13 consecutive HIV+/HCV+ recipients were identified. Median time of post‐transplant follow‐up was 722 days. Seven patients were transplanted in the DAA era; five of them had anti‐HCV Ab+ donors, with two donors being HCV NAT positive; all received DAA therapy, six of them post‐transplant (median time from KT to DAA: 83 days; IQR, 54‐300). All the patients in the pre‐DAA era were on a protease inhibitor‐containing ART regimen. One‐year patient and death‐censored graft survivals were 83% and 67%, respectively, for the patients transplanted in the pre‐DAA era, and 100% for both outcomes in the subgroup of patients transplanted in the post‐DAA era ( P > 0.05). Compared to patients in the post‐DAA era, those in the pre‐DAA era had higher incidence of serious infections (0 vs 67%; P = 0.02). Acute rejection exclusively occurred in the pre‐DAA group (n = 1; 17%). Conclusions: Outcomes of HIV+/HCV+ KT recipients, including HIV−/HCV+ to HIV+/HCV+ transplants, in the DAA era were excellent in this small cohort. Larger studies are needed.